Risk, concentration and market power in the banking industry : evidence from the Colombian System (1997-2006) (2007)
This paper examines the relationship between risk, concentration and the exercise of market power by banking institutions. We use monthly balance-sheet and interest rate data for the Colombian banking system from 1997 to 2006. The evidence shows that, in the face of high risk, banks transfer a larger share of risk to customers through higher intermediation margins. The result suggests that systemic risk acts as a "collusion" device for banks: while high concentration is not enough to have collusion, the true effects of high market concentration on interest rates' mark-ups emerge when the system is under stress.